Development of binders for textile reinforced concrete. (2021) - Mohan, A.; Madhavi, T.Ch.
Abstract: The current study focuses on minimizing the waste at is generated as part of the industrial process. These wastes are disposal becomes a major threat to the environment. As a measure to utilize these wastes as a construction material. The current study utilizes fly ash and silica fume as part of binder mixes that have been investigated. The major objective of the study is to examine the mechanical strength of two unique inorganic cementitious binders mixes along with a convention binder mix. The inorganic cementitious binders were used for bonding textile-reinforced concrete along with the concrete surface. The mixed ratio of the binder is 1:3 with water to binder ratio of 0.4. two different binder mixes M1 (cement, Quartz powder, and silica fume) and M2 (cement/Ground Granular Blast Slag). A compressive test has been conducted for binder mixes as per codes. An 18 number of cubes of size 70.6 mm were cast and tested at the end of the 7th and 28th days of curing. It is observed that the M2 binder mix was found to increase in compressive strength and was compared with a conventional binder and modified binder mixes. When compared with conventional binder mix, modified binder M2 was increased by 62.5% and 39.17% of compression strength.